Validating the usefulness of the NSI validity-10 with the MMPI-2-RF. (1st September 2020) - Gradwohl, Brian D.; Mangum, Ryan W.; Tolle, Kathryn A.; Pangilinan, Percival H.; Bieliauskas, Linas A.; Spencer, Robert J.
Abstract: Purpose/Aim of the Study: The Neurobehavioral Symptom Inventory (NSI) is a 22-item self-report measure created to quantify the somatosensory, cognitive, and affective symptoms of Post-concussive Syndrome. Developers of the NSI used a subset of 10 items, the Validty-10, to measure symptom overreporting. We compared the Validity-10 versus the remaining NSI items (i.e., the Remaining-12) for how accurately they detect symptom exaggeration on the Minnesota Multiphasic Personality Inventory Second Edition - Restructured Form (MMPI-2-RF). Materials and Methods: We used a sample of 45 veterans evaluated in a Polytrauma/TBI Clinic of a Midwest VA Healthcare System who completed the NSI and MMPI-2-RF. Results: The Vaidity-10, Remaining-12, and Total Score all strongly correlated with mean of the MMPI-2-RF validity scales ( r  = .65, .67, and .70, respectively), illustrating equivalency among the various NSI scores. Groups were created based on significant T score elevation on any MMPI-2-RF validity scale (i.e. F- r  > 119, or Fp-r, F-s, FBS, or RBS > 99). ROC analyses demonstrated that areas under the curve were equivalent for NSI Total Score (.84), Validity-10 (.81), and Remaining-12 (.81) in detecting overreporting. Conclusions: These findings do not support the notion that the Validity-10 has unique utility as an embedded symptom validity scale and highlights the likelihood that NSI Total Score can also serve this function.